Effectiveness of interventions to reduce child marriage and teen pregnancy in sub-Saharan Africa: A systematic review of quantitative evidence - Feyissa, Garumma Tolu; Tolu, Lemi Belay; Soboka, Matiwos; Ezeh, Alex (Frontiers in Reproductive Health, 2023)
Introduction: Early marriage and teen pregnancy have negative health, social and development consequences. Highest rates of child marriage occur in sub-Saharan Africa (SSA) and 40% of women in Western and Central Africa got married before the age of 18. This systematic review was aimed to fill a gap in evidence of effectiveness to reduce teen pregnancy and early marriage in SSA. Methods: We considered studies that reported on early marriage and teen pregnancy for inclusion. We searched PubMed, EMBASE, CINAHL, Web of Science, Science Direct, Cochrane Database of Systematic Reviews (CENTRAL) and grey literature sources. Results: We included 30 articles in this review. We categorized the interventions reported in the review into five general categories: a) Interventions aimed to build educational assets, b) Interventions aimed to build life skills and health assets, c) Wealth building interventions, and d) Community dialogue. Only few interventions were consistently effective across the studies included in the review. The provision of scholarship and systematically implemented community dialogues are consistently effective across settings. Conclusion: Program designers aiming to empower adolescent girls should address environmental factors, including financial barriers and community norms. Future researchers should consider designing rigorous effectiveness and cost effectiveness studies to ensure sustainability.